Pengaruh Pendekatan Client Centered terhadap Konsep Diri Siswa di Sekolah SMP Islam Al-Ulum Terpadu Medan - Sri Hariati Harahap; Alfin Siregar; Ali Daud Hasibuan (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This research aims to examine the influence of the client-centered approach on students’ self-concept at Al-Ulum Terpadu Islamic Middle School, Medan. The main focus of this research is to evaluate whether the application of counseling techniques based on a client-centered approach can improve students’ self-concept compared to the control group who did not receive treatment. This research is a quantitative research using a quasi experimental method (quasi experimental design) with a two group design (between subject design). The population of this research was 53 students from classes IX-B and X-D. The sample used was purposive sampling. So 10 research samples were taken with a high level of saturation, namely 5 students from the experimental group (IX-B) and 5 children from the control class (IX-D). The research instrument used here is in the form of a questionnaire. The results of this study show that preliminary data shows that before treatment, the majority of students were in the low category (< 76%) in self-concept, with the experimental group showing two students in the low category while the control group were all in the high category (> 79%) . After implementing the client centered approach in group counseling, the experimental group showed significant improvements; only one student was still in the low category, while the control group remained in the high category without any significant changes. The results of this study concluded that the client centered approach was effective in increasing students’ self-concept, in contrast to the control group which did not show changes in self-concept categories. This research confirms the importance of applying client-centered counseling techniques in an educational context to improve students’ self-concept.